Identification and analysis of the young population in the starburst galaxy NGC 253 - Rodríguez, María Jimena (2018)
We present a study of the young population in the starburst galaxy NGC 253. In particular, we focused our attention on searching young star groups, obtaining their main properties and studying their hierarchical organization. For this task, we used multiband images and their corresponding photometric data obtained with the Advanced Camera for Surveys of the Hubble Space Telescope (ACS/HST).We have first derived the absorption affecting the different regions of the galaxy. Then, we applied an automatic and objective searching method over the corrected data in order to detect young star groups. We complemented this result with the construction of the stellar density map for the blue young population. A statistical procedure to decontaminate the photometric diagrams from field stars was applied over the detected groups and we estimated their fundamental parameters.As a result, we built a catalog of 875 new identified young groups with their main characteristics, including coordinates, sizes, estimated number of members, stellar densities, luminosity function (LF) slopes and galactocentric distances. We observed these groups delineate different structures of the galaxy, and they are the last step in the hierarchical way in which the young population is organized. From their size distribution, we found they have typical radius of ∼ 40 − 50 pc. These values are consistent with those ones found in others nearby galaxies. We estimated a mean value of the LF slope of 0.21 and an average density of 0.0006 stars/pc³ for the identified young groups taking into account stars earlier than B6.